Post‐traumatic stress as a determinant of quality of life in pediatric solid‐organ transplant recipients. (26th March 2021) - Hind, Tatsuma; Lui, Samantha; Moon, Erin; Broad, Katherine; Lang, Samantha; Schreiber, Richard A.; Armstrong, Kathryn; Blydt‐Hansen, Tom D.
Abstract: Living with end‐stage organ failure is associated with an accumulation of traumatic medical events, and despite recovery after solid‐organ transplantation (SOT), many children continue to exhibit lower quality of life (QOL). Few studies have examined the relationship between post‐traumatic stress disorder (PTSD) and QOL among pediatric SOT recipients. We conducted a retrospective, cross‐sectional review of 61 pediatric SOT recipients (12 heart, 30 kidney, and 19 liver) to evaluate the association of PTSD with self‐reported QOL. PTSD was measured by the Child Trauma Screening Questionnaire (CTSQ), and QOL was measured using the PedsQL and PedsQL Transplant Module (PedsQL‐TM) surveys. Demographics, baseline, and contemporaneous factors were tested for independent association. SOT recipients were 15.2 (12.1–17.6) years old at survey completion. Median CTSQ score was 2 (1–3), highest in kidney recipients, and 13% were identified as high risk for PTSD. Median PedsQL score was 83 (70–91) and significantly associated with the CTSQ score ( r = −.68, p < .001). Median PedsQL Transplant Module score was 89 (83–95) and similarly associated with the CTSQ score ( r = −.64, p < .001). Age at time of surveys and presence of any disability were also independently associated with PedsQL and PedsQL‐TM, respectively. When adjusted for Emotional Functioning, CTSQ remained associated with PedsQL subscores ( r = −.65, p < .001). Trauma symptoms are a major modifiable risk factor for lower self‐perceived QOL and represent a potentially important target for post‐transplant rehabilitation. Additional research is needed to understand the root contributors to PTSD and potential treatments in this population.